Coxiella burnetii, the agent of Q fever in Brazil: its hidden role in seronegative arthritis and the importance of molecular diagnosis based on the repetitive element IS1111 associated with the transposase gene - Tatiana Rozental; Luis Filipe Mascarenhas; Ronaldo Rozenbaum; Raphael Gomes; Grasiely Souza Mattos; Cecília Carlos Magno; Daniele Nunes Almeida; Maria Inês Doria Rossi; Alexsandra RM Favacho; Elba Regina Sampaio de Lemos (Memorias do Instituto Oswaldo Cruz, 2012)
Coxiella burnetii is the agent of Q fever , an emergent worldwide zoonosis of wide clinical spectrum. Although C. burnetii infection is typically associated with acute infection, atypical pneumonia and flu-like symptoms, endocarditis, osteoarticular manifestations and severe disease are possible, especially when the patient has a suppressed immune system; however, these severe complications are typically neglected. This study reports the sequencing of the repetitive element IS1111 of the transposase gene of C. burnetii from blood and bronchoalveolar lavage (BAL) samples from a patient with severe pneumonia following methotrexate therapy, resulting in the molecular diagnosis of Q fever in a patient who had been diagnosed with active seronegative polyarthritis two years earlier. To the best of our knowledge, this represents the first documented case of the isolation of C. burnetii DNA from a BAL sample.